Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yanru Fang*; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai* (Energy Policy, 2023)
Road transportation accounts for 56% of India's transportation sector's CO2 emissions. Reaching carbon neutrality before 2070 requires the deep decarbonization of this sector. This study assesses the potential of battery electric vehicles (BEV) and fuel-cell vehicles (FCV) as the least-cost pathway toward carbon neutrality. We estimate the future demand for passenger and freight services and evaluate the impact of EV policies using the Integrated Model of Energy, Environment, and Economy for Sustainable Development/Technology (IMED/TEC). The study covers road transport emissions, energy, and air pollution transitions under four scenarios, including reference, low, medium, and high penetration of BEV and FCV, which align with the decarbonization target agreed upon under India's national policy. Results show that the carbon neutrality target would be challenging with BEV alone in road passenger and freight transportation because it is less efficient. Combined penetration of BEV and FCV can reduce air pollutant emissions significantly. Operative implementation of FCV could diminish more than 96% of the total road transport CO2 emissions. The analytical framework also proposes local climate change policies towards a carbon neutrality strategy to escalate the share of BEV and FCV in the Indian road transport sector.
Keywords: Air Pollutants; Carbon neutrality; Co-benefits; Electric vehicle; electricity; Hydrogen; India